2000
DOI: 10.1071/pp99057
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene inhibitors improve dry matter partitioning and development of late flowering spikelets on rice panicles

Abstract: Primary branch development of the rice panicle was in the order of a basipetal sequence from the top to the bottom at the time of anthesis. Delayed development of spikelets on the proximal branches of the panicle resulted in reduced grain filling. Two experiments were carried out to manipulate growth and development of the proximal spikelets with exogenous application of chemicals regulating formation or action of ethylene. In the first experiment, inhibitors of ethylene synthesis (cobalt) and action (silver) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…There are instances other than rice, where ethylene action was reported antagonistic to that of cytokinin (Kudryakova et al 2001) because production of the former in plant tissue promotes inactivation of the latter (Tarverner et al 1999). In rice, ethylene impedes dry matter partitioning Mohapatra et al 2000) and seed coat development (Mohapatra and Mohapatra 2006) more in the basal spikelet than in the apical spikelet, resulting in poor filling of grains (Mohapatra et al 1993). Thereby, the apical spikelets exert dominance in rates of growth and cell division in the endosperm over the basal spikelets (Yang et al 2006).The dominance of the top spikelets in accumulation of dry matter or cell number, an opposing trend in ethylene formation (Table 3) indicate that auxin could also be involved in the difference of grain filling between spikelets.…”
Section: Discussionmentioning
confidence: 95%
“…There are instances other than rice, where ethylene action was reported antagonistic to that of cytokinin (Kudryakova et al 2001) because production of the former in plant tissue promotes inactivation of the latter (Tarverner et al 1999). In rice, ethylene impedes dry matter partitioning Mohapatra et al 2000) and seed coat development (Mohapatra and Mohapatra 2006) more in the basal spikelet than in the apical spikelet, resulting in poor filling of grains (Mohapatra et al 1993). Thereby, the apical spikelets exert dominance in rates of growth and cell division in the endosperm over the basal spikelets (Yang et al 2006).The dominance of the top spikelets in accumulation of dry matter or cell number, an opposing trend in ethylene formation (Table 3) indicate that auxin could also be involved in the difference of grain filling between spikelets.…”
Section: Discussionmentioning
confidence: 95%
“…There are reports that high levels of ethylene and 1-aminocylopropane-1-carboxylic acid (ACC), a precursor of ethylene, have frequently been related to abortion in maize (Zea Mays) (Cheng and Lur 1996) and reduction in grain weight of wheat (Triticum aestivum) (Beltrano et al 1994;Yang et al 2006a) and rice (Yang et al 2006b). Application of ethylene inhibitors improved dry matter partitioning and development of laterflowered spikelets on rice panicles (Mohapatra et al 2000). In contrast to ethylene, high levels of free PAs, spermidine (Spd, 3-amine), and spermine (Spm, 4-amine), but not putrescine (Put, diamine), are observed to be closely associated with higher kernel set and better seed development in maize (Sen et al 1981;Lin et al 1984;Feng et al 2011) and a greater grain filling rate in rice (Yang et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…In support of these observations, reductions in grain filling rate and weight due to increases in ethylene under conditions of water stress have been reported in wheat [70] and rice [34], while [71] and Naik and Mohapatra (2000) [72] observed that application of ethylene inhibitors on rice improved grain filling and enhanced sucrose synthase activity under conditions of water stress. In accordance to the above reports, in our study application of 1-MCP had a pronounced effect on pistil sucrose concentration, signifi-cantly inhibiting sucrose accumulation under water-stress compared to the untreated water-stressed plants.…”
Section: Discussionmentioning
confidence: 50%